Transformation towards sustainable and resilient societies in Asia and the Pacific. (Regional cooperation strategy and programs., 2018)
The report takes stock of the changing nature of risk in Asia and the Pacific, and the stresses, shocks and opportunities that are affecting a diverse regions prospects for achieving the sustainable development goals (SDGs). It quantifies the effects of selected natural hazards, commodity shocks and pollution shocks on the regions fundamental human systems. It highlights practical efforts being made by citizens, civil society, government and the private sector to build resilience capacities. It urges attention on the need to strengthen our ability to transform our societies if we are to achieve the SDGs. This joint report is a contribution to the ongoing regional and global dialogue on pathways to achieving sustainable development.